High-Sensitivity Sandwich ELISA for Plasma NT-proUcn2: Plasma Concentrations and Relationship to Mortality in Heart Failure. (6th January 2020) - Liew, Oi Wah; Yandle, Timothy G; Chong, Jenny P C; Ng, Yan Xia; Frampton, Christopher M; Ng, Tze Pin; Lam, Carolyn S P; Richards, A Mark
Abstract: BACKGROUND: Urocortin 2 (Ucn2) has powerful hemodynamic, renal, and neurohormonal actions and likely participates in normal circulatory homeostasis and the compensatory response to heart failure (HF). A validated assay for endogenous circulating Ucn2 would facilitate investigations into Ucn2 physiology and elucidate its derangement and potential as a biomarker in heart disease. METHOD: We developed a chemiluminescence-based sandwich ELISA to measure plasma N-terminal (NT)-proUcn2 in non-HF patients (control; n = 160) and HF patients with reduced (HFREF; n = 134) and preserved (HFPEF; n = 121) left ventricular ejection fraction (LVEF). RESULTS: The ELISA had a limit of detection of 8.47 ng/L (1.52 pmol/L) and working range of 23.8–572 ng/L. Intra- and interassay CV and total error were 4.8, 16.2, and 17.7%, respectively. The median (interquartile range) plasma NT-proUcn2 concentration in controls was 112 (86–132) ng/L. HFREF, HFPEF, and all HF plasma concentrations were significantly increased [117 (98–141) ng/L, P = 0.0007; 119 (93–136) ng/L, P = 0.0376, and 119 (97–140) ng/L, P = 0.001] compared with controls but did not differ significantly between HFREF and HFPEF. NT-proUcn2 was modestly related to age ( r = 0.264, P = 0.001) and cardiac troponin T ( r = 0.258, P = 0.001) but not N-terminal pro-B-type natriuretic peptide, body mass index, LVEF, or estimated glomerular filtration rate. On multivariate analysis, plasma NT-proUcn2 was independently and inversely related to 2-year mortality in HF. CONCLUSIONS: The validated ELISA measured human NT-proUcn2 in plasma and showed modest but significant increases in HF patients compared with controls. In HF, the unusual inverse relationship between plasma NT-proUcn2 and 2-year mortality portends potential prognostic value but requires further corroboration.